Responses of Physiology, Photosynthesis, and Related Genes to Saline Stress in Cornus hongkongensis subsp. tonkinensis (W. P. Fang) Q. Y. Xiang - Jia-Qiu Yuan; Da-Wei Sun; Qiang Lu; Ling Yang; Hao-Wei Wang; Xiang-Xiang Fu (Plants, 2022)
Cornus hongkongensis subsp. tonkinensis (W. P. Fang) Q. Y. Xiang is a native evergreen species with high ornamental value for abundant variations in leaf, bract, fruit, and tree gesture. To broaden its cultivation in coastal saline soil, salt damage and survival rate, physiological responses, photosynthetic performance, and related genes were evaluated for annual seedlings exposed to 0.3% salt (ST) concentrations for 60 days. Syndromes of salt damage were aggravated, and the survival rate decreased with prolonged stress duration; all stressed seedlings displayed salt damage, and 58.3% survived. Under short-term saline stress (5 d), marked increases in malondialdehyde (MDA), relative electrical conductivity (REC), and decreases in superoxide dismutase (SOD), photosynthetic rate (Pn), stomatal conductance (gs), and internal carbon dioxide concentration (Ci) were recorded. The stable leaf water use efficiency (WUE) and chlorophyll content were positive physiological responses to ensure photosynthetic performance. Meanwhile, the expression levels of genes related to photosystem II (psbA) and photorespiration (SGAT and GGAT) were upregulated, indicating the role of photorespiration in protecting photosynthesis from photoinhibition. After 30 days of stress (≥30 d), there was a significant increase in MDA, REC, soluble sugar (SS), soluble protein (SP), and Ci, whereas descending patterns in Pn, gs, WUE, the maximal photochemical efficiency of photosystem II (Fv/Fm), and potential activities of PSII (Fv/F0) occurred in salt-stressed seedlings, compared with CK. Meanwhile, the expression levels of related genes significantly dropped, such as psbA, LFNR, GGAT, GLYK, and PGK, indicating photoinhibition and worse photosynthetic performance. Our results suggest that the moderate salt tolerance of C. hongkongensis subsp. tonkinensis mostly lies in a better photosynthetic system influenced by active photorespiration. Hence, these results provide a framework for better understanding the photosynthetic responses of C. hongkongensis subsp. tonkinensis to salt stress.